2002
DOI: 10.1007/s00421-002-0663-8
|View full text |Cite
|
Sign up to set email alerts
|

Differences in leg muscle activity during running and cycling in humans

Abstract: Delta (D) efficiency is defined as the ratio of an increment in the external mechanical power output to the increase in metabolic power required to produce it. The purpose of the present study was to investigate whether differences in leg muscle activity between running and cycling can explain the observed difference in D efficiency between the two activities. A group of 11 subjects performed incremental submaximal running and cycling tests on successive days. The D efficiencies during running and cycling were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(65 citation statements)
references
References 32 publications
(33 reference statements)
2
48
1
Order By: Relevance
“…Although there are no studies evaluating the impact of different mode of aerobic exercises (cycling, running, rowing etc.) on the subsequent strength exercise performance, it is possible to infer that the cycling exercise result in higher local fatigue than running (Bijker et al, 2002), although a chronic study demonstrated the opposity, in which the interference generated by running exercise was greater than that generated by cycling when compared to strength training only (Gergley, 2009). …”
Section: Volume 7 | Issue 4 | 2012 | 821 Discussionmentioning
confidence: 99%
“…Although there are no studies evaluating the impact of different mode of aerobic exercises (cycling, running, rowing etc.) on the subsequent strength exercise performance, it is possible to infer that the cycling exercise result in higher local fatigue than running (Bijker et al, 2002), although a chronic study demonstrated the opposity, in which the interference generated by running exercise was greater than that generated by cycling when compared to strength training only (Gergley, 2009). …”
Section: Volume 7 | Issue 4 | 2012 | 821 Discussionmentioning
confidence: 99%
“…Nevertheless, theoretically impossible efficiency values indicate a flaw in the calculations. For example, Bijker et al (2001Bijker et al ( , 2002 report a delta efficiency for running of around 50%, which seems to be an unlikely, if not impossible, true efficiency. Note that we do not claim that the use of delta efficiency is meaningless; rather we claim that it is not a measure for efficiency.…”
Section: Delta Efficiencymentioning
confidence: 93%
“…In cycling, this requirement is fulfilled by using the same cadence. Furthermore, it is expected that the energy cost-work rate relationship is linear, which has been substantiated empirically in many studies (e.g., Bijker et al 2001Bijker et al , 2002Chavarren and Calbet 1999;HintzyCloutier et al 2003;Widrick et al 1992; see also the literature results gathered in this review, Fig. 2), although it should be noted that for sustained work rates that exceed the lactate threshold this relationship may become nonlinear because of the influence of the so-called ''slow component'' of oxygen uptake (e.g., Poole et al 1994;Whipp and Rossiter 2005).…”
Section: Internal Work and Work Efficiencymentioning
confidence: 95%
See 2 more Smart Citations